Identifying the Impact of Culturally Relevant Pedagogy: Evidence of Academic Risk-Taking in Culturally and Economically Diverse Nova Scotia Classrooms - Mitton, Jennifer; Murray-Orr, Anne (Canadian Journal of Education/Revue canadienne de l'éducation, 2021)
This article reports on findings from a qualitative research study investigating ways to support learners from populations who have been historically underserved by the Nova Scotia education system, particularly African Nova Scotian and Mi’kmaq learners, and learners who experience poverty. Working with middle school teachers located in rural schools with a proven track record of enabling students to succeed and thrive, we spent two years in their classrooms observing and documenting pedagogical practices in the teaching of science and social studies. The results of this research not only complement what is known about how to support vulnerable learners in diverse school contexts, but also provide insights into how these teachers created conditions in which students felt able to take risks academically. The findings of this study show how the idea of academic risk-taking can complement, and expand, scholarship on culturally relevant pedagogy. Cet article rend compte des résultats d’une recherche qualitative étudiant les moyens de soutenir les apprenants issus de populations historiquement mal desservies par le système éducatif de Nouvelle-Écosse, plus particulièrement ceux d’origine africaine et Mi’kmaq, ainsi que ceux qui vivent dans la pauvreté. En partenariat avec des enseignants du secondaire d’écoles rurales ayant fait leurs preuves en matière de réussite et d’épanouissement des élèves, nous avons passé deux ans à observer et à consigner les pratiques pédagogiques adoptées en classe dans leur enseignement des sciences et des études sociales. Les résultats de cette recherche, en plus d’enrichir les connaissances sur la manière de soutenir les apprenants vulnérables dans divers contextes scolaires, apportent des indications sur la manière dont ces enseignants ont réussi à créer des conditions dans lesquelles les élèves se sentent capables de prendre des risques sur le plan scolaire. Enfin, cette étude démontre comment la notion de prise de risques sur le plan scolaire peut parfaire et élargir l’éventail des ...